REGIONAL TASK WITH UNLOCAL CONDITION AND TASK OF OPTIMUM MANAGEMENT FOR LINEAR PARABOLIC EQUALIZATIONS WITH DEGENERATION - Пукальський, Іван Дмитрович; Ісарюк, І. М. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
In spaces of classic functions with sedate weight the existence and unique of decision of the first parabolic regional task is led to with an integral condition after a sentinel variable for linear differential equalization with sedate features on co-ordinate planes. Got result is drawn on for research of tasks of optimum management.